Executive functions and working memory in motor control: Does the type of MCI matter?. Issue 6 (1st November 2020) - Rajtar-Zembaty, Anna; Rajtar-Zembaty, Jakub; Sałakowski, Andrzej; Starowicz-Filip, Anna; Skalska, Anna
Abstract: The purpose of this study was to evaluate the association between functional mobility performance and executive functions in older adults with the amnestic (aMCI) and nonamnestic (naMCI) type of mild cognitive impairment (MCI), as well as in a control group. A cross-sectional study was conducted among 800 older adults (147 with MCI) who participated in a longitudinal study consisting in an interdisciplinary geriatric assessment and rehabilitation program in Kraków. Motor performance was measured with the Timed Up and Go test (TUG), while standard neuropsychological tests were used to assess different cognitive domains. Analysis of the entire sample showed that almost all cognitive domains and the presence of MCI are associated with functional mobility. Executive functions, letter fluency, and working memory were associated with TUG in the MCI group. The MCI type was not a significant moderator of the relationship between cognitive and motor performance. In group analyses, various cognitive predictors for TUG in the aMCI group, naMCI, and control group were demonstrated. Our results suggest that executive functions and working memory in aMCI and letter fluency in naMCI are independently associated with functional mobility performance. Executive functions are important for gait control in MCI.